Creating a High‐Trust Organization: An Exploration into Organizational Policies that Stimulate Interpersonal Trust Building - Six, Frédérique; Sorge, Arndt (Journal of Management Studies, 2008)
abstract We examine empirically how an organization that deliberately enhances interpersonal trust to become a significant organizational phenomenon, is different from a similar organization without explicit trust enhancement policies. The point of departure is relational signalling theory, which says that trust is a function of consistently giving off signals that indicate credible concern, to potential trustors. A matched pair of two consulting organizations, with different trust policies but otherwise similar characteristics, were studied intensively, using survey research, participant observation and half‐open interviewing, focused on the generation of trust and the handling of trouble when trust was threatened or destroyed. A higher stage of trust can be reached by an inter‐related set of policies: promoting a relationship‐oriented culture, facilitation of unambiguous signalling, consistent induction training, creating opportunities for meeting informally, and the day‐to‐day management of competencies. Such policies are in principle independent of recognized contextual contingencies.